Natural attractions in the area Gandoca National Wildlife Refuge Gandoca Manzanillo, Limón, Costa Rica - Rojas-Jiménez, Karla (2016)
The physical planning is an element contributing to the socioeconomic development. Within this process, the determination of ecotourism attractions in protected wilderness areas of mixed character is essential to guide the permitted uses and community management. This study aimed to identify the natural attractions Gandoca sector, the National Wildlife Refuge Gandoca Manzanillo, Limon, Costa Rica. To which a participatory workshop was held with various community sectors and members of management of the refuge. Additionally, field visits were conducted, guided by members of the community and the validation of the attractions with the participation of key informants. Each was georeferenced and characterized based on the methodology proposed by the Costa Rican Tourism Institute (ICT). We determined the presence of the following types of attractions: coast, mountain, coastal lagoon, mangrove, cativales, wildlife sightings with emphasis on sea turtles, among others. On the issue of sea turtles, the most important is the leatherback turtle sightings. From these attractions which turned out to be more important or valued was the sighting of flora and fauna. The attraction won the highest ranking (5) was wildlife sightings while which had the lowest hierarchy (1) was the beach. The most important attraction for the community was the sea turtle sightings followed the mangroves. We conclude that in this area there are 10 types of natural attractions and tourist activity has been focused on the leatherback turtle. These elements identified should be incorporated into a management proposal to promote local development.